Two-Dimensional Fatigue Crack Growth Analysis Using Extended Finite Element Method (XFEM) - Muhammad Shafeeq, Abdul Hannan (Universiti Sains Malaysia, 2018)
This thesis proposes the ability an improved FEM technique known as extended finite element method (XFEM) to analyse fatigue crack growth under constant amplitude loading. This thesis compares numerically modelled crack propagation in a bending steel specimen with experimentally conducted and simulated previously using traditional FEM technique. The aim of the study was to perform numerical analysis of crack propagation in order to determine the shape of the crack extension. Model of the test specimen was prepared based on geometric parametres and cyclic load condition. The numerical analysis was performed using Abaqus 6.12-2. Crack propagation was simulated by using the numerical extended finite element method (XFEM) under low-cycle fatigue criterion using direct cyclic approach. This thesis, verifies the validity of this numerical method for crack propagation. The numerical results of the direction of the crack propagation were compared with the experimental findings in a real specimen and previously simulated using adapative technique method in the literature [1]. The outcome of the proposed method is not as what was expected due to the crack propagation was not like illustrated in the literature. It is shown that the computed crack path does not justify the previous findings.